METHODOLOGY FOR IMPROVING PEDAGOGICAL MECHANISMS OF THE EDUCATIONAL PROCESS IN DEVELOPING LANGUAGE COMPETENCIES OF FUTURE TEACHERS - Khasanova Madina (Ta’lim innovatsiyasi va integratsiyasi, 2026)
This article highlights the issues related to improving the pedagogical mechanisms used in the process of developing language competencies of future teachers. The effectiveness of modern language-teaching technologies, the competency-based approach, the use of digital resources, and interactive methods is scientifically analyzed. Additionally, methodical recommendations aimed at enhancing language competencies are presented.